Analisis Pengakuan Negara dan Perlindungan Hak Asasi Manusia Terhadap Individu Transgender di Indonesia (International Forum of Researchers and Lecturers, 2024)
Transgenders are a minority group in society who are vulnerable to discrimination. This research aims to analyze whether the state's recognition and protection arrangements for transgender individuals in Indonesia are in accordance with human rights principles, and also to analyze how the ideal legal construction for transgender individuals is in accordance with human rights principles. In this research, the research method used is normative legal research with a conceptual and comparative approach. The results of the research obtained are that in general Indonesia has regulated the protection of human rights for Indonesian people in accordance with human rights principles. However, in this case the legal culture of Indonesian society is one of the factors why discrimination against transgender individuals still often occurs. So it is necessary to establish an ideal legal construction that is expected to be beneficial for all parties, in this context beneficial for society in general and transgender individuals in particular. An understanding of the principles of balanced human rights is needed to maintain stability in society. An in-depth study of transgender is also needed to understand and to be able to provide effective solutions in handling the transgender phenomenon in Indonesia.